2017
DOI: 10.18632/oncotarget.18817
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AQP3 and CD24 as biomarkers for carcinogenesis of gastric intestinal metaplasia

Abstract: Gastric intestinal metaplasia (GIM) is a precancerous gastric carcinoma (GC) lesion with pivotal roles in carcinogenesis. CD24, LGR5 and Ki67 are expressed in GIM; we previously demonstrated that aquaporin 3 (AQP3) is expressed in goblet cells and is positively correlated with GIM severity. However, the relationships of AQP3 with GIM classification and with other proteins, and their roles in the transition from GIM to gastric carcinoma (GC) remain unknown. Sixteen patients with intestinal-type GC were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…A previous study showed that AQP3 is expressed in goblet cells and is positively correlated with gastric intestinal metaplasia (GIM) severity [45]. In addition, it has been found that AQP3 is highly expressed in GC tissues and regulates the proliferation, migration and invasion of human GC cells through a variety of signaling pathways [42].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that AQP3 is expressed in goblet cells and is positively correlated with gastric intestinal metaplasia (GIM) severity [45]. In addition, it has been found that AQP3 is highly expressed in GC tissues and regulates the proliferation, migration and invasion of human GC cells through a variety of signaling pathways [42].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer (GC) is one of the most common diagnosed cancers worldwide and the third leading cause of cancer-related mortality after lung and liver cancer (Ferlay et al, 2015). The carcinogenesis and progression of GC is complex, involving the alternations of multi-step and multi-genes (Zhao et al, 2017). The 5-year survival rate of GC diagnosed at a later stage is less than 20%, but rises to 90% for patients diagnosed at an early stage (Stahl et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence from AQP3 −/− mice and AQP3-knockdown cells for the involvement of AQP3 in various inflammatory diseases including atopic dermatitis, psoriasis, allergy, and cancer progression, in which AQP3 transport function supported cell proliferation, migration, and inflammation [22][23][24][25][26]42,57,58 . Also, many descriptive studies have shown positive correlations between AQP3 expression and cancer progression and prognosis [59][60][61][62][63][64][65] . Thus, AQP3 inhibition has been suggested as a potential therapeutic target for a variety of diseases.…”
Section: Discussionmentioning
confidence: 99%